Association between serum soluble (pro)renin receptor level and worsening of cardiac function in hemodialysis patients: A prospective observational study. - Yoshifumi Amari; Satoshi Morimoto; Takeshi Iida; Hiroki Takimoto; Hidenobu Okuda; Takatomi Yurugi; Yasuo Oyama; Naoki Aoyama; Fumitaka Nakajima; Atsuhiro Ichihara (PLoS ONE, 2020)
The (pro)renin receptor ((P)RR) is cleaved to generate soluble (P)RR (s(P)RR), which reflects the status of the tissue renin-angiotensin system. Hemodialysis (HD) patients have a poor prognosis due to the increased prevalence of cardiovascular diseases. The present study aimed to investigate whether serum s(P)RR level is associated with the worsening of cardiac function in HD patients. A total of 258 maintenance HD patients were recruited and serum s(P)RR concentration was measured. Background factors in patients who survived (S group) and patients who died (D group) during the 12-month follow-up period and relationships between serum s(P)RR level and changes in cardiac function during the follow-up period in the S group were investigated. The median serum s(P)RR value at baseline was 29.8 ng/ml. Twenty-four patients died during the follow-up period. Cardiothoracic ratio, human atrial natriuretic peptide (hANP), brain natriuretic peptide (BNP), and E over e-prime were significantly higher in the D group. In the S group, changes in hANP or BNP were significantly greater in the higher serum s(P)RR group than in the lower serum s(P)RR group. High serum s(P)RR level was significantly correlated with changes in BNP, independent of other factors. High serum s(P)RR level was associated with increases in BNP, independent of other risk factors, suggesting that an increased expression of (P)RR may be associated with a progression of heart failure in HD patients and that serum s(P)RR concentration could be used as a biomarker for selecting patients requiring intensive care.